Combined mercury removal and low-temperature NH3-SCR OF NO with MnOx/TiO2 sorbents/catalysts. Issue 8 (3rd August 2018) - Cimino, S.; Mangone, C.; Scala, F.
ABSTRACT: MnO x /TiO2 catalysts/sorbents were investigated for flue gas purification via the simultaneous low-temperature NH3 -SCR of NO and elemental Hg capture, in the temperature range 25–300°C. In particular, the effects of the Mn precursor salt (acetate vs. nitrate) and of the TiO2 support textural properties (nanotubes vs. random mesopores) on both DeNO x and Hg capture efficiencies were addressed. The catalysts/sorbents were also characterized by means of ICP-MS, SEM-EDX, XRD, BET, H2 -TPR, NH3 adsorption, and temperature programmed desorption of both NH3 and Hg. Catalysts prepared by acetate precursor generally displayed a higher reducibility at low temperature which translated into a higher oxidation activity, enhancing mercury capture rate, but adversely affecting the selectivity of the selective catalytic reduction (SCR) process at temperatures above 150°C. Hg was effectively captured up to 250°C and stored on the sorbent in an oxidized form. The original sorption properties could be fully restored by a simple thermal treatment in air at temperatures ≤500°C, releasing elemental mercury. The textural properties of the support were found to have a limited impact on both the Hg capture and SCR performance.